#UsefulScience: National Science and Technology Week in rural schools - Regina Célia Sousa; Carolina Pereira Aranha; André Flávio Gonçalves Silva; Juliana Rodrigues Rocha (Universidade Federal do Norte do Tocantins, 2019)
This article reports on the execution of the #Useful Science project, part of the National Science Science Week (SNCT) of 2017. This project was executed in five rural schools in the micro-region of the Middle Mearim (MA), by teachers and students of the Federal University of Maranhão. The activities developed consisted of eleven workshops and a photographic exhibition, through which information and applications of scientific research associated with popular knowledge were presented to the public formed by the school and local communities, seeking to arouse their attention to the resulting effects of the natural sciences and mathematics in your daily life. In addition, children and young people were encouraged to seek new knowledge and scientific and technological careers. The project had a significant participation of the faculty, students and administrators of the schools served, as well as the community in its surroundings. During its execution, 715 citizens were served. After the final evaluations, we verified that the activities accomplished reached their objectives, contributing to the expansion of the understanding about science and technology, detected through the recognition of their relevance and the connections made with their realities.